2018
DOI: 10.1590/1518-8345.2755.3071
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic load and canine companionship: a comparative study using biomarkers in older adults

Abstract: Objective:to compare the biomarkers and the allostatic load levels in a sample of older persons with and without canine companionship. Method:descriptive and comparative study. Data were collected using a sociodemographic questionnaire and a fasting blood sample. The allostatic load comprised 11 biomarkers that are primary and secondary stress mediators, which arise from the following systems: neuroendocrine, immune, metabolic, cardiovascular and anthropometric. Results:a significant difference was found in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Data from a representative longitudinal study on older adults [143] showed that high allostatic load levels were associ ated with several personality characteristics (neuroticism, lower extroversion, lower conscientiousness) at baseline, and with declines in extroversion, conscientiousness, agreeableness and openness at a 4year followup. Older adults with canine companionship displayed lower levels of allostatic load compared to those without [144].…”
Section: Agingmentioning
confidence: 84%
“…Data from a representative longitudinal study on older adults [143] showed that high allostatic load levels were associ ated with several personality characteristics (neuroticism, lower extroversion, lower conscientiousness) at baseline, and with declines in extroversion, conscientiousness, agreeableness and openness at a 4year followup. Older adults with canine companionship displayed lower levels of allostatic load compared to those without [144].…”
Section: Agingmentioning
confidence: 84%
“…Also, psychological benefits from the relationship to the pet are reported, especially in older adults [36]. Dog owners report fewer depression and anxiety symptoms, and improved social contacts [37] and positive emotions [38,39]. Another study showed that dog and cat ownership was not directly associated with psychological wellbeing [10].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy to reduce stress is through positive relationships, including with a companion animal, such as a dog. For example, Morales-Jinez et al (2018) compared two groups of older adults who lived with and without canine companions and found reduced levels of cortisol and total cholesterol, biomarkers associated with stress, in participants who owned dogs [ 7 ]. These differences are likely due in part to lifestyle differences: dog owners have been shown to exercise more often and sleep better [ 8 ].…”
Section: Introductionmentioning
confidence: 99%